Occupational Asbestos-containing Materials Exposure and Risk of Asbestosis among Construction Workers - Ridho, Fiki Muhammad; Ghani, Hafid Nur; Laksono, Eko Puji; Faisal, Ahmad; Nurrahman, Hafidz Arafath (Penerbit Goodwood, 2024)
Purpose: Asbestos-containing materials are often found at construction sites, and long-term exposure to accumulated asbestos can increase the risk of asbestos-related diseases, including asbestosis. The present study aimed to further describe the exposure to asbestos in construction workers and the risk of asbestosis, as well as the management and prevention of asbestos exposure. Methodology: The narrative review method was used to conduct this study with a comprehensive literature search of the following databases: PubMed, Scopus, ScienceDirect, and Google Scholar. Results: According to the review, we finally found that many materials in the construction sector contain asbestos and have the potential to spread asbestos fibers into the air and can be inhaled by workers. Cumulative asbestos exposure that occurs in high doses over a long period of time will cause an increases the risk of asbestos-related diseases, including asbestosis. Apart from asbestos exposure, several other factors, such as genetics, smoking, sex, age, and physiology, are closely related to the occurrence and development of asbestosis. The construction sector has the highest exposure to asbestos compared to other sectors or industries and has a high number of asbestosis cases. Thus, it is necessary to provide precautions for workers, such as the use of adequate personal protective equipment of international standards, the presence of health inspectors, and routine checks on workers' health, as well as management of materials or construction waste containing asbestos. Limitations: This study is limited to describing general exposure to asbestos-containing materials and the increased risk of asbestosis in construction workers. Future research regarding further analysis of causal factors, management, and prevention of asbestos exposure, as well as case reports and mapping of asbestosis cases, especially in Indonesia, where related research is still limited, may be warranted. Contribution: This review can be used as a basic reference for conducting further research regarding asbestos exposure to workers and the prevention and management of asbestos-containing materials at construction sites.